2017
DOI: 10.5194/hess-21-345-2017
|View full text |Cite
|
Sign up to set email alerts
|

Formulating and testing a method for perturbing precipitation time series to reflect anticipated climatic changes

Abstract: Abstract. Urban water infrastructure has very long planning horizons, and planning is thus very dependent on reliable estimates of the impacts of climate change. Many urban water systems are designed using time series with a high temporal resolution. To assess the impact of climate change on these systems, similarly high-resolution precipitation time series for future climate are necessary. Climate models cannot at their current resolutions provide these time series at the relevant scales. Known methods for st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Here, no correction is applied to GCM precipitation projections. Instead, the relative change between the historical and scenario simulations of the GCM is used to calculate a change factor that can then be applied to the observed time series (Sunyer et al, 2012(Sunyer et al, , 2015. The method applied to the precipitation P of day t in month m Table 1.…”
Section: Change Factor Of Mean (Cfm) Methodsmentioning
confidence: 99%
“…Here, no correction is applied to GCM precipitation projections. Instead, the relative change between the historical and scenario simulations of the GCM is used to calculate a change factor that can then be applied to the observed time series (Sunyer et al, 2012(Sunyer et al, , 2015. The method applied to the precipitation P of day t in month m Table 1.…”
Section: Change Factor Of Mean (Cfm) Methodsmentioning
confidence: 99%
“…The author showed that synthetic but high-resolution time series could be used to assess the probability distribution of the variables and predict short-term operation rules and hydropower generation, which are crucial for securing WRM. The climate change impacts on these time series were also considered in recent studies (Pereira-Cardenal et al 2014;Sørup et al 2017). Sechi et al (2019) used the stochastic quasi-gradient method to optimize and simulate a pumping system's often conflicting water deficit and energy consumption.…”
Section: Reservoirs and Hydropower Plantsmentioning
confidence: 99%
“…Furthermore, they define several classes of dry spell lengths (Table 4), based on the percentiles of dry spell length calculated using the historical period of the study. Dry spells are not to be confused with the terms dry events (Willems, 2013;Willems and Vrac, 2011) or inter-events (Sørup et al, 2017;Thorndahl et al, 2017) used in the SDMs. This is due to the definition of dry spells comprising consecutive dry days (≥ 2 days).…”
Section: Research Indicatorsmentioning
confidence: 99%